The Role of Literacy Events in Developing Iraqi’s EFL Skills: A Descriptive Study - Al-Asadi, Fatimah (Al-Adab Journal, 2025)
Literacy events extract meaning from many sources including written ones. EFL learners might not be aware of the several activities, other than learning, that can help improve their language skills. The current quantitative descriptive study investigated the utilization of English sources outside the classroom. A total of (48) participant answered the survey of this study. The results of the study showed few participants use the target language in their daily life while the majority of the sample use literacy events outside the classroom with a variety of impact of developing their language domains. The study is important for Iraqi EFL teachers because it can be helpful in designing extracurricular activities in the EFL classroom.